Twelve new Demospongiae (Porifera) from Chilean fjords, with remarks upon sponge-derived biogeographic compartments in the SE Pacific - Hajdu, Eduardo; Desqueyroux-Faúndez, Ruth; Carvalho, Mariana De Souza; Lôbo-Hajdu, Gisele; Willenz, Philippe (Zootaxa, 2013)
This article reports on 12 new species originating from the Chilean fjords region, namely Clathria (Microciona) mytilifila sp. nov., Haliclona (Reniera) caduca sp. nov., Latrunculia (L.) ciruela sp. nov., Latrunculia (L.) copihuensis sp. nov., Latrunculia (L.) verenae sp. nov., Latrunculia (L.) yepayek sp. nov., Myxilla (Burtonanchora) araucana sp. nov., Neopodospongia tupecomareni sp. nov., Oceanapia guaiteca sp. nov., Oceanapia spinisphaera sp. nov., Suberites cranium sp. nov. and Tethya melinka sp. nov. The material studied was collected between 5 and 30 m depth at latitudes comprised between 42º and 50ºS, and is part of a large collection of Chilean sponges gathered by an international team in a series of expeditions. Identification keys are provided for SE Pacific Suberites and Latrunculia, and the known species of Myxilla (Burtonanchora) and Neopodospongia. A trans-Pacific link to the New Zealand fauna was retrieved for the latter genus. Distribution ranges apparent from the materials studied here are judged too preliminary to allow any inference on biotic boundaries in the SE Pacific. A revision of earlier assertions about these biogeographic units and their boundaries concluded that very little support remains other than for existence of a Magellanic fauna. This is in part a consequence of revising the taxonomy of sponge species originally deemed to underpin these areas. Specifically, the former proposal of a Central to Southern Chile biogeographic unit (33–56ºS) has been markedly undone.